Effect Of Alcohol Abuse On Human Cognition - Yahaya, Azizi (2008)
Malaysia is the tenth largest consumer of alcohol in the world and so few studies have been carried to find the precise magnitude of the problems caused by this consumption.The facts and figures shows that it is increasing each year. Alcohol abuse in Malaysia is mainly heavy intake in the form of drinks, underage drinking and driving under the influence of alcohol. This is due to the ready availability of alcohol and the cheap price which is affordable by many. The main effect of alcohol in humans is the brain which is the â€œcentral processing mechanismâ€? for cognitive processes such as perception, attention, consciousness, thinking, storing and retrieval of memory, cognition development, problem solving and intelligence.The effects can be short term or lasting implications not only to the drinkers but their family and their country. Everyone should be aware of the adverse effects of alcohol especially to children since their brain are still developing and are subject to environmental stimulation. Educating the people is one way to eradicate alcohol abuse. All religions forbid the drinking of alcohol because of its effects on our mental and psychological health.